2015
DOI: 10.1038/srep07639
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of exosome purification methods using a model liposome system and tunable-resistive pulse sensing

Abstract: Exosomes are vesicles which have garnered interest due to their diagnostic and therapeutic potential. Isolation of pure yields of exosomes from complex biological fluids whilst preserving their physical characteristics is critical for downstream applications. In this study, we use 100 nm-liposomes from 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) and cholesterol as a model system as a model system to assess the effect of exosome isolation protocols on vesicle recovery and size distribution using a single-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
189
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(196 citation statements)
references
References 29 publications
3
189
2
2
Order By: Relevance
“…Comparative results of UC are difficult to obtain due to the high number of models available in the market, and this could affect the quality of the isolated product [43]. The use of a fixed instrument would keep low variability between batches [47]. …”
Section: Semi-synthetic Exosomes: Biotechnological Modification Of Namentioning
confidence: 99%
“…Comparative results of UC are difficult to obtain due to the high number of models available in the market, and this could affect the quality of the isolated product [43]. The use of a fixed instrument would keep low variability between batches [47]. …”
Section: Semi-synthetic Exosomes: Biotechnological Modification Of Namentioning
confidence: 99%
“…Additionally, the impact of the high shear forces on the vesicle integrity are under debate. While some studies indicate no changes in the integrity of the EVs after UC [68,69] others show subtle EV aggregation influencing the EV biodistribution [70,71].…”
Section: Ev Purification Protocols and Stabilitymentioning
confidence: 99%
“…As a result, there have been a surge in the number of diagnostic modalities to study EVs. Over the last few years, a number of studies have employed TRPS as a diagnostic tool to characterise EVs [48][49][50][51][52].…”
Section: Trps In Extracellular Vesicles Analysismentioning
confidence: 99%
“…Lane et al [50] studied the effects of various exosome isolation protocols on vesicle recovery and size distribution using TRPS and 100nm liposomes as a model system, shown in figure 5. They demonstrated that liposome size distribution and ζ-potential are comparable to those of extracted exosomes, making them an ideal model for comparison studies.…”
Section: Trps In Extracellular Vesicles Analysismentioning
confidence: 99%